Successful conversion surgery for locally advanced gallbladder cancer after gemcitabine and nab-paclitaxel chemotherapy - Yang, Ziyi; Wu, Ziyou; Xiong, Yichen; Liu, Shilei; Cai, Chen; Shao, Ziyu; Zhu, Yidi; Song, Xiaoling; Shen, Wei; Wang, Xuefeng; Wu, Xiangsong; Gong, Wei (Frontiers in Oncology, 2022)
Objective: Gallbladder cancer (GBC) is highly malignant and is often diagnosed at advanced stage. Lack of opportunity to surgery results in unsatisfactory outcome. This pilot study employed gemcitabine combined with nab-paclitaxel (AG) as conversion therapeutic measure for locally advanced GBC and successfully achieved conversion surgery in three initially unresectable GBC patients. We will introduce our experience on improving the outcome of this dismal disease. Methods: Radiology and nuclear medicine image were performed in each patient and resectability was evaluated by jointed consultation of our multi-disciplinary team (MDT). Patients evaluated as unresectable were treated with AG regimen and re-evaluated for treatment response. When complete or partial response achieved, MDT opinion would be required to assess the possibility of performing conversion surgery with R0 resection. Results: Three GBC patients which initially evaluated as unresectable were successfully underwent R0 resection after conversion therapy with AG regimen. The first case was a recurrent GBC patient evaluated as locally advanced and eventually achieved pathological complete response. The second case was a GBC patient underwent R1 resection with residual lesions in gallbladder bed and isolated No.16 lymph nodes metastasis which had pathological complete response after treatment. The third case had multiple but resectable liver metastases, both objective response and partial pathologic response were achieved. None of the patients experienced serious treatment-related adverse events. All cases revealed no evidence of recurrence or metastasis after a median follow-up of 12 months. Conclusions: Conversion therapy shows a favorable efficacy in those unresectable GBC patients. Gemcitabine plus nab-paclitaxel has the potential to be used as preoperative treatment options for GBC patients at advanced stage. To further explore the efficacy of AG on conversion therapy for GBC patients, a prospective clinical trial has been registered (ChiCTR2200055698).